Research on Repeatability of Liquid Filling Mass Based on Weighing Method. (April 2020) - Li, Bin; Gou, Yang; Chen, Jie; Fan, Xinghang; Cheng, Shuo
Abstract: The traditional dynamic flow controller has the problems of high conductivity, poor system stability and measurement accuracy. In this paper, the filling time of the liquid is controlled by the 0330 electromagnetic valve of Burkert company in Germany; the electronic balance is verified by the 100g weight of F2 grade of China Shuiling weight factory; the liquid mass after filling is measured by the bt4202s electronic balance of Sartorius company in Germany, and the repeatability of the experimental analysis of the liquid quality after filling is carried out. The experimental results show that the liquid filling mass of the device has high repeatability. It solves the problem of low repeatability of small flow liquid filling mass and has high application value.